Comparative Analysis of Virulence Mechanisms of Trypanosomatids Pathogenic to Humans - de Castro Neto, Artur Leonel; da Silveira, José Franco; Mortara, Renato Arruda (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma brucei, Leishmania spp., and T. cruzi are flagellate protozoans of the family Trypanosomatidae and the causative agents of human African trypanosomiasis, leishmaniasis, and Chagas disease, respectively. These diseases affect humans worldwide and exert a significant impact on public health. Over the course of evolution, the parasites associated with these pathologies have developed mechanisms to circumvent the immune response system throughout the infection cycle. In cases of human infection, this function is undertaken by a group of proteins and processes that allow the parasites to propagate and survive during host invasion. In T. brucei, antigenic variation is promoted by variant surface glycoproteins and other proteins involved in evasion from the humoral immune response, which helps the parasite sustain itself in the extracellular milieu during infection. Conversely, Leishmania spp. and T. cruzi possess a more complex infection cycle, with specific intracellular stages. In addition to mechanisms for evading humoral immunity, the pathogens have also developed mechanisms for facilitating their adhesion and incorporation into host cells. In this review, the different immune evasion strategies at cellular and molecular levels developed by these human-pathogenic trypanosomatids have been discussed, with a focus on the key molecules responsible for mediating the invasion and evasion mechanisms and the effects of these molecules on virulence.